Teaching and learning of Geographical Information Systems (GIS) in South African Secondary Schools - Sefara, Phetla Jacob (My University, 2017)
Teaching and learning of Geographical Information Systems (GIS) in the Secondary Schools of South Africa has some challenges that the Department of Basic Education must attend to. The purpose of this study was to explore how GIS technology can be taught and learnt in secondary schools in South Africa. GIS is a technology that combines hardware, software, data, people, procedures and arrangement of collecting, storing, manipulating, analysing and displaying information about spatially distributed phenomena for the purpose of making a decision or solving a problem. This technology is in fact a decision support system. It was initially taught and learnt only in institutions of higher learning. It was only recently, from around 1991, that some countries introduced it into the geography curriculum of secondary schools. It started in the secondary schools of developed countries, such as the United States of America, United Kingdom and Canada. When the National Curriculum Statement (NCS) for Geography at Further Education and Training (FET) Band for Grades 10 – 12 was implemented in South Africa in 2006, GIS was then introduced into the geography curriculum. In the same year, GIS was introduced in Grade 10, the following year in Grade 11 and Grade 12 in 2008. The research study was done in one hundred secondary schools in the five districts of Limpopo Province. The research study used mixed methods in collecting and analysing data. Quantitative and qualitative data was collected in the form of a questionnaire and interviews. Learners in selected secondary schools were also given a test on GIS to assess their GIS knowledge. Data analysed indicate that GIS teachers are keen to be trained so that they could know how to teach it. Young teachers trained recently seem to know it because they were exposed to it during their training at universities. The only major obstacle is unavailability of teaching and learning resources. The study recommends that private cooperates and big businesses should participate in alleviating the shortage of hardware and software in South African secondary schools. Technology must play a key role in schools because of the technological innovations the world is experiencing.
Thesis ( Ph.D. (Education)) -- University of Limpopo, 2017
Keywords: Technology; Secondary school; Geographical Information Systems; Geographic information systems; Education, Secondary; Teaching -- Aids and devices